Molecular characteristics of rotavirus genotypes circulating in the south of Benin, 2016–2018 - Agbla, Jijoho Michel (BMC Res Notes, 2020)
OBJECTIVE: Rotavirus remains the main causative agent of gastroenteritis in young children in countries that have not yet introduced the vaccine. In Benin, rotavirus vaccine was introduced late December 2019 into the EPI. This study aims to provide pre-vaccination era rotavirus genotyping data in Benin. These data can supplement data from the surveillance system of Ministry of Health of Benin which is supported by the World Health Organization (WHO). RESULTS: Of the 420 diarrheal stool samples, actively collected in southern Benin from July 2016 through November 2018 from children under 5 years old and suffering from gastroenteritis, 167 (39.8%) samples were rotavirus EIA positive. 186 (44.3%) samples contained amplifiable rotavirus RNA detected by qRT-PCR method and were genotyped using one-step RT-PCR multiplex genotyping method. G1P[8] represents the predominant genotype (32%) followed by the G2P[4] (26%), G3P[6] (16%), G12P[8] (13%) and mixed G and P types (1%). Four samples (2%) could not be assigned both G and P type specificity.